Penerapan Teori Service Dominan Logic pada Wisata Arung Jeram Vertical Rafting Magelang Dalam Perspektif Maqashid Syariah - Ustadz, Damar Irsyad; Purwanto; Pudail (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Dominant Logic Perspective is a marketing strategy. The dominant perspective of Logic consists of 8 aspects, namely operating means, resource acquisition, services and experiences, value plans, dialogue, value creation networks, and marketing cooperation. This study examines the extent to which the Magelang Vertical Rafting Rafting Tour is implemented in a marketing perspective based on the service concept to determine the marketing strategy used by the company. This type of research is descriptive research with a qualitative approach method. The results of this study indicate that the Magelang Vertical Rafting Rafting Tour implements the concept of service dominant logic in 8 existing aspects according to the principles of Maqashid Syariah. Only, of course, there is 1 aspect that has not been maximized, namely the aspect of Operational Resources, so a strategy is needed to increase the number of employees to help expedite the operation of services. Kata kunci: Operational resources, Service Dominant Logic, Strategy, Tourism